El dibujo y la pintura como herramienta pedagógica para el desarrollo de la psicomotricidad de los estudiantes de 6to año de educación general básica en la unidad educativa “23 de abril” de la parroquia Santa Fe de la ciudad de Guaranda provincia Bolívar, durante el año 2022 - Quilligana Reinoso, Willan Rene (2022)
The purpose of this research work was established with the theme: "Drawing and painting as a pedagogical tool for the development of psychomotor skills in students of 6th year of General Basic Education of the Educational Unit April 23 of the Santa Fe parish, in the city of Guaranda, Bolivar province, during the year 2022, since it lacks primary needs related to drawing and painting as a pedagogical tool due to the little applicability, in addition, it does not allow effective learning in students. This led this project to take due importance and make significant changes in this classroom, for this reason, it was proposed as a general objective to determine that drawing and painting as a pedagogical tool allows the development of psychomotor skills in the students, since, The application of a drawing and painting test was used to measure the skills and abilities that they possessed, thus identifying the degree of skills and abilities, to which a drawing and painting workshop guide was elaborated, which developed the psychomotor skills of the children in the sixth year of General Basic Education of the establishment previously mentioned. The theoretical framework helps us to demonstrate and comply with the variables of our research work, in addition, we have the legal theory that is based on the Constitution of Ecuador, which came into force in 2008, as well as the referential theory where the creation and importance of this educational institution is marked, in addition, We also have the results where the value of this work is clearly highlighted and finally we present the proposal where we propose the following guide of basic techniques of artistic drawing and painting to raise the psychomotor skills which was applied in children to verify the veracity of our work and the importance of drawing with children.